2016
DOI: 10.1016/j.bpj.2015.11.3518
|View full text |Cite
|
Sign up to set email alerts
|

Desmin Mutation in the C-Terminal Domain Impairs Traction Force Generation in Myoblasts

Abstract: The cytoskeleton plays a key role in the ability of cells to both resist mechanical stress and generate force, but the precise involvement of intermediate filaments in these processes remains unclear. We focus here on desmin, a type III intermediate filament, which is specifically expressed in muscle cells and serves as a skeletal muscle differentiation marker. By using several complementary experimental techniques, we have investigated the impact of overexpressing desmin and expressing a mutant desmin on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 45 publications
3
24
0
3
Order By: Relevance
“…About 30% of the cells contain both a network and cytoplasmic aggregates of desmin. The features of this aggregation are specific to the E413K desmin mutation as previously described [Levin et al., ; Chourbagi et al., ; Charrier et al., ]. The presence of aggregates does not correlate with a high GFP signal: some very fluorescent cells do not show aggregates, whereas less fluorescent ones display aggregates, pointing out that the aggregation of desmin‐E413K‐GFP is not related to its over‐expression but to its dominant negative properties.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…About 30% of the cells contain both a network and cytoplasmic aggregates of desmin. The features of this aggregation are specific to the E413K desmin mutation as previously described [Levin et al., ; Chourbagi et al., ; Charrier et al., ]. The presence of aggregates does not correlate with a high GFP signal: some very fluorescent cells do not show aggregates, whereas less fluorescent ones display aggregates, pointing out that the aggregation of desmin‐E413K‐GFP is not related to its over‐expression but to its dominant negative properties.…”
Section: Resultssupporting
confidence: 56%
“…We focus here on the E413K mutation of desmin, a point mutation located at the beginning of the C‐terminal domain of the protein that disturbs its assembly into filaments in vitro [Bär et al., ; Levin et al., ], and leads to skeletal muscle weakness in patients [Pruszczyk et al., ]. We have recently shown that the expression of E413K‐mutated desmin in cellulo at the early stage of myoblasts alters these cells ability to generate traction forces [Charrier et al., ]. We question here the impact of this mutation on the viscoelastic properties of myoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Desmin has multiple critical roles in muscle cells [9,13]. Previous research has confirmed that desmin plays a significant role in the organization and assembly of sarcomeres [14]; the first discovery of the DES mutation was made in desmin-related myofibrillar myopathy patients exhibiting a skeletal-muscle-restricted phenotype [8].…”
Section: Discussionmentioning
confidence: 99%
“…Desmin is expressed early in cardiac development, it is the major muscle-specific intermediate filament protein, and it is highly expressed in heart tissue [8,9,13]. Mutations in DES are highly capable of leading to heart disorders.…”
Section: Discussionmentioning
confidence: 99%
“…To begin to understand intercytoskeletal communications, we focused on muscle desmin and actin, which are involved in force‐related events and in the scaffolding of the complex muscle architecture (Charrier et al, ; Leccia et al, ; Palmisano et al, ). The interaction of desmin filaments with muscle proteins of nebulin and nebulette contributes to the organization of the Z‐disk structure, and the modulation of their affinity by desmin mutations can induce dysfunction of striated muscle cells (Baker et al, ; Hernandez et al, ).…”
Section: Introductionmentioning
confidence: 99%